The twentieth anniversary of the journal: editor's introduction - Zavadskas, Kazimieras; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2014)
„The twentieth anniversary of the journal: editor's introduction" Technological and Economic Development of Economy, 20(2), p. 181-183